Templated versus non-templated synthesis of benzo-21-crown-7 and the influence of substituents on its complexing properties - Jiang, Wei; Schalley, Christoph A. (Beilstein Journal of Organic Chemistry, 2010)
Two procedures for the synthesis of benzo-21-crown-7 have been explored. The [1+1] macrocyclization with KBF4 as the template was found to be more efficient than the intramolecular macrocyclization without template. Pseudorotaxanes form with secondary ammonium ions bearing at least one alkyl chain narrow enough to slip into the crown ether. Substitution on benzo-21-crown-7 or on the secondary ammonium axle alters the binding affinity and binding mode. Compared to dibenzo-24-crown-8, the complexing properties of benzo-21-crown-7 turn out to be more susceptible to modifications at the crown periphery.
Keywords: benzo-21-crown-7; pseudorotaxane; self-sorting; supramolecular chemistry; template